PROPHETIC PRACTICES IN HUMAN RESOURCE MANAGEMENT - Kamal Bangash, Faisal Mohammed Musaddiq (IJRDO - Journal of Social Science and Humanities Research, 2024)
Traditionally, the main motive behind focusing on human resources is organizations’ strivingto achieve the maximum profits possible. While the Islamic motives are focusing on caringabout the human resource as a human being whom was created to be Allah's deputy on earth.Prophet Mohammed PBUH came with a message that made working have a religious value.Separating work from its Islamic values stopped it from being the biggest motive for human’sdevelopment in organizations. Prophet Mohammed PBUH came with a message that honoredhumans and made their practical development a great concern, motivating them to buildingvalues, behaviors, improving performance, achieving and managing goals. The Prophet PBUHcame with great values that would advance the idea of human resources management andenhance the human being in the organization, which would reflect on his performance andachieving the goals and objectives of organizations. This research claims that the impact of the1prophetic applications on human resources is more comprehensive, spacious in scope and hasgreater impact than traditional human resources management. This research can be a scientificand practical reference to highlight the mechanisms and practicesfound from Prophet’s sayings,actions, or from the Sharia he brought in.